Effect of Dietary Essential Oils Supplementation on Growth Performance, Nutrient Utilization, and Protein Digestibility of Juvenile Gilthead Seabream Fed a Low‐Fishmeal Diet. Issue 4 (11th January 2018) - Rodrigues, Vera; Colen, Rita; Ribeiro, Laura; Santos, Gonçalo; Gonçalves, Rui A.; Dias, Jorge
Abstract: The present study aimed to assess the efficacy of supplemental plant essential oils (PEOs) on the growth performance and digestive processes of juvenile gilthead seabream. Three experimental diets were tested: (1) a control (CTRL) diet formulated with low marine‐derived protein level (19%); (2) CTRL diet supplemented with a blend of anise, citrus, and oregano essential oils at 1.2 g/kg (diet Phyto C); and (3) CTRL diet supplemented with a similar blend at 0.2 g/kg, but in encapsulated form (diet Phyto E). Triplicate groups of 20 fish (mean initial body weight = 27.9 ± 2.1 g) were fed the experimental diets over 63 d. Results showed that specific growth rate, voluntary feed intake, feed conversion ratio, and protein efficiency ratio were not significantly affected by the two dietary supplements. The commercial blend of PEOs tested here can be successfully incorporated into a low‐fishmeal diet to maximize protein and fat retention and to minimize nitrogenous losses in seabream juveniles. Phyto E presented a decrease in nitrogenous metabolic and fecal losses. The practical implications of including this plant‐based blend in aquafeeds can potentially include faster fish growth and improved production time, but these remain to be tested in a longer experimental trial.